The birth of piRNAs: how mammalian piRNAs are produced, originated, and evolved - Sun, Yu H.; Lee, Brent; Li, Xin Zhiguo (Mammalian genome, 2022)
PIWI-interacting RNAs (piRNAs), small noncoding RNAs 24–35 nucleotides long, are essential for animal fertility. They play critical roles in a range of functions, including transposable element suppression, gene expression regulation, imprinting, and viral defense. In mammals, piRNAs are the most abundant small RNAs in adult testes and the only small RNAs that direct epigenetic modification of chromatin in the nucleus. The production of piRNAs is a complex process from transcription to post-transcription, requiring unique machinery often distinct from the biogenesis of other RNAs. In mice, piRNA biogenesis occurs in specialized subcellular locations, involves dynamic developmental regulation, and displays sexual dimorphism. Furthermore, the genomic loci and sequences of piRNAs evolve much more rapidly than most of the genomic regions. Understanding piRNA biogenesis should reveal novel RNA regulations recognizing and processing piRNA precursors and the forces driving the gain and loss of piRNAs during animal evolution. Such findings may provide the basis for the development of engineered piRNAs capable of modulating epigenetic regulation, thereby offering possible single-dose RNA therapy without changing the genomic DNA. In this review, we focus on the biogenesis of piRNAs in mammalian adult testes that are derived from long non-coding RNAs. Although piRNA biogenesis is believed to be evolutionarily conserved from fruit flies to humans, recent studies argue for the existence of diverse, mammalian-specific RNA-processing pathways that convert precursor RNAs into piRNAs, perhaps associated with the unique features of mammalian piRNAs or germ cell development. We end with the discussion of major questions in the field, including substrate recognition and the birth of new piRNAs.